2017
DOI: 10.1108/ebhrm-03-2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Demographic challenges for the future business leader: evidence from a Greek survey

Abstract: Purpose The purpose of this paper is to identify the challenges posed to business leaders from major global demographic changes expected in the workforce composition, such as higher participation of women and more active involvement of elder and more experienced people in the future workforce. Design/methodology/approach The authors ran a survey among 733 middle managers, focusing on their ideal leadership behavior. The Global Leadership and Organizational Behavior project methodology was applied for data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The results indicated that for each unit increase in future orientation, there was an expected increase of 0.300 in women’s leadership effectiveness. This result was consistent with past studies (Abu-Jarad et al , 2010; Galanaki and Papalexandris, 2017;). In addition, Seginer et al (1991) found that women scored significantly higher than men on identity commitment, future education and future career orientation.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The results indicated that for each unit increase in future orientation, there was an expected increase of 0.300 in women’s leadership effectiveness. This result was consistent with past studies (Abu-Jarad et al , 2010; Galanaki and Papalexandris, 2017;). In addition, Seginer et al (1991) found that women scored significantly higher than men on identity commitment, future education and future career orientation.…”
Section: Resultssupporting
confidence: 94%
“…Several women academic leaders clarified that the Saudi Vision for 2030 will open many opportunities for Saudi women who have long awaited such an opportunity, claiming that it will allow Saudi women to occupy positions of leadership in the country in the coming years. As women constituted 50% of university graduates, women supported this vision through long-term strategic orientation and giving a higher priority to long-term success (Abu-Jarad et al , 2010; Galanaki and Papalexandris, 2017; Ozgen, 2012). In addition, female academicians tend to display visionary leadership that can identify patterns in the face of chaos and uncertainty, which will ultimately help them get the opportunity to lead universities more effectively (Galanaki and Papalexandris, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of gender egalitarianism and related constructs can be very complex. There are many antecedents that drive cross-cultural differences in the division of roles between the sexes (Abu-Jarad et al, 2010; Galanaki and Papalexandris, 2017;Ozgen, 2012;House et al, 2004). The antecedents include attitudes, stereotypes, parental investment, religion, economic development, and even climate and geographical latitude.…”
Section: Introductionmentioning
confidence: 99%